EFFECTS OF SUPPLY CHAIN DIGITAL TWINS IN THE DEVELOPMENT OF DIGITAL INDUSTRY - Simchenko, N.A; Tsohla, S.Y; Chuvatkin, P.P (International Journal of Supply Chain Management, 2020)
Abstract? The article is devoted to the study of the effect types of supply chain digital twins implementation in branches of industry. For the purposes of this article, the problem of implementing supply chain digital twins is considered in terms of the interests of various stakeholders and their contribution to the development of the supply chain Digital Twins market. The study of Digital Twins effects analysed the indicators of digital business transformation. It is proved that the digital transformation of Russian industry should be directly linked to the development of Digital Twins. Based on the analysis of the effects of Digital Twins development in the automotive, petrochemical, oil and gas, transport, and construction industries, a map representing the relation between interests of stakeholders and their contribution to the development of the Digital Twins market has been developed. This map contains both the interests of key stakeholders in the Digital Twins market and their possible contribution to the interests of each stakeholder group. The developed methodological toolbox is an important component of the formation of institutional support measures by the state for the development of the digital industry.